Composition of Suberin Extracted upon Gradual Alkaline Methanolysis of Quercus suber L. Cork - Lopes, Marta H.; Gil, Ana M.; Silvestre, Armando J. D.; Neto, Carlos Pascoal (Journal of Agricultural and Food Chemistry, 2000)
The monomeric composition of suberin extracts obtained by gradual alkaline methanolysis of Quercus suber cork was determined by gas chromatography?mass spectrometry (GC-MS). Results show that 1-alkanols and alkanoic and α,?-alkanedioic acids are preferentially removed upon mild alkaline conditions, whereas mid-chain-modified ?-hydroxyalkanoic acids are preferentially removed under stronger alkaline conditions. Saturated ?-hydroxyalkanoic acids are found to be abundant in all suberin extracts. These results are consistent with two distinct suberin fractions with different locations in cork cell walls and/or esterification degrees. It is proposed that these fractions correlate with the two main suberin peaks in the solid state 13C NMR spectra of cork and suberin extracts. Quantitative GC-MS analysis showed that suberin monomers comprise ?30% (w/w) of the suberin extracts, the remaining comprising nonvolatile structures with high Mn values, as measured by vapor pressure osmometry. The presence of a large fraction of high molecular weight aliphatic structures in suberin extracts is supported by the corresponding NMR spectra. Keywords: Suberin; cork; Quercus suber L.; GC-MS; NMR; alkaline methanolysis
doi: 10.1021/jf9909398doi: 10.1021/jf9909398The following values have no corresponding Zotero field: publisher: American Chemical Society
Keywords: Alkaline methanolysis; Cork; GC-MS; NMR; Quercus suber L.; suberin

Cork suberin as a new source of chemicals. 1. Isolation and chemical characterization of its composition. - Cordeiro, N.; Belgacem, M. N.; Silvestre, a J.; Pascoal Neto, C.; Gandini, A. (International journal of biological macromolecules, 1998)
Extractive-free cork from Quercus suber L. was submitted to a solvolysis treatment with methanolic NaOH which yielded 37% (o.d. cork) of suberin. This mixture of compounds was thoroughly characterized by FTIR, 1H- and 13C-NMR, gas chromatography coupled with mass spectrometric (GC-MS) analysis, vapour pressure osmometry (VPO), mass spectrography (MS) and gel permeation chromatography (GPC). After derivatization, the main components of the volatile fraction, representing less than half of the total, were found to be omega-hydroxymonocarboxylates, alpha, omega-dicarboxylates, simple alkanoates and 1-alkanols, all with chain lengths ranging from C16 to C24. A second fraction, with an average molecular weight about three times higher, was detected by VPO, MS and GPC. The presence of this important fraction in cork suberin had not been recognized in earlier studies. Both fractions constitute interesting precursors for the elaboration of new materials.
The following values have no corresponding Zotero field: accession-num: 9585884
Keywords: Alkaline methanolysis; Chemical characterization; Cork; Molecular weight distribution; Quercus suber L.; suberin

Cork suberin as a new source of chemicals. 1. Isolation and chemical characterization of its composition. - Cordeiro, N; Belgacem, M N; Silvestre, a J; Pascoal Neto, C; Gandini, A (International journal of biological macromolecules, 1998)
Extractive-free cork from Quercus suber L. was submitted to a solvolysis treatment with methanolic NaOH which yielded 37% (o.d. cork) of suberin. This mixture of compounds was thoroughly characterized by FTIR, 1H- and 13C-NMR, gas chromatography coupled with mass spectrometric (GC-MS) analysis, vapour pressure osmometry (VPO), mass spectrography (MS) and gel permeation chromatography (GPC). After derivatization, the main components of the volatile fraction, representing less than half of the total, were found to be omega-hydroxymonocarboxylates, alpha, omega-dicarboxylates, simple alkanoates and 1-alkanols, all with chain lengths ranging from C16 to C24. A second fraction, with an average molecular weight about three times higher, was detected by VPO, MS and GPC. The presence of this important fraction in cork suberin had not been recognized in earlier studies. Both fractions constitute interesting precursors for the elaboration of new materials.
Keywords: Alkaline methanolysis; Chemical characterization; Cork; Molecular weight distribution; Quercus suber L.; suberin

Cork suberin as a new source of chemicals: 2. Crystallinity, thermal and rheological properties - Cordeiro, N; Belgacem, N M; Gandini, A; Neto, C P (Bioresource technology, 1998)
Suberin samples, obtained by alkaline methanolysis from cork (Quercus suber L.), were submitted to various physical characterizations; DSC, TGA, optical microscopy, density and rheological properties. A sub- stantial proportion of these oligomers possessed a microcrystalline character with a melting range between 0 and 50°C. The amorphous part was liquid at room temperature and did not display a detectable glass transition upon cooling because of its wide molecular weight distribution. The viscous behaviour of suberin at room temperature was both plastic and thixotropic because of the structuring role of the micro- crystals
Keywords: Alkaline methanolysis; cork of Quercus suber L.; crystallinity; Density; rheological properties; suberin; thermal characterization

Cork suberin as a new source of chemicals: 2. Crystallinity, thermal and rheological properties - Cordeiro, N.; Belgacem, N. M.; Gandini, A.; Neto, C. P. (Bioresource technology, 1998)
Suberin samples, obtained by alkaline methanolysis from cork (Quercus suber L.), were submitted to various physical characterizations; DSC, TGA, optical microscopy, density and rheological properties. A sub- stantial proportion of these oligomers possessed a microcrystalline character with a melting range between 0 and 50°C. The amorphous part was liquid at room temperature and did not display a detectable glass transition upon cooling because of its wide molecular weight distribution. The viscous behaviour of suberin at room temperature was both plastic and thixotropic because of the structuring role of the micro- crystals
Keywords: Alkaline methanolysis; cork of Quercus suber L.; crystallinity; Density; rheological properties; suberin; thermal characterization